Manipulations of feed ration and rearing density : effects on river migration performance of Atlantic salmon smolt - Royan, Mansour (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
The out-migration of Atlantic salmon smolts was studied at the lower part of the Umeå River (River Umeälven) from the Norrfors dam towards the sea (Bothnian Bay) in northern Sweden. Two-year old hatchery-reared Atlantic salmon (n=250) were tagged with acoustic transmitters and released downstream of the Norrfors dam and monitored while migrating downstream. The aim of this study was to determine the effects of feed restriction and rearing density on the migratory behaviour of Atlantic salmon smolts in the lower part of the flow-controlled river Umeälven in northern Sweden.